Shelf-life extension of leavened bakery products by using bio-protective cultures and type-III sourdough. (1st March 2023) - Calasso, Maria; Marzano, Marinella; Caponio, Giusy Rita; Celano, Giuseppe; Fosso, Bruno; Calabrese, Francesco Maria; De Palma, Domenico; Vacca, Mirco; Notario, Elisabetta; Pesole, Graziano; De Angelis, Maria; De Leo, Francesca
Abstract: Physicochemical and microbiological alteration of processed foods limits their shelf-life. To extend the shelf-life of two different types of bakery products, we evaluated the effectiveness of a type-III sourdough (tIII-SD) combined with a mixture of probiotics ( Lactobacillus acidophilus, L. casei, Bifidobacterium spp, Bacillus coagulans ) that were used as bioprotective-cultures (BCs). This innovative (I) dough was used to produce fresh base-pizza (BP) and focaccia (FO) that were inspected by a multi-omics approach aimful at monitoring features at different time-points of the shelf-life. Differences in physicochemical, protein, microbiological and volatile profiles were also investigated after 10-days of extended shelf-life. The addition of BCs and tIII-SD left unchanged the proximate composition. This, together with the absence of detected microbial contaminations, indicated the suitability of both I-BP and I-FO despite the shelf-life extension. Both I-samples accounted for a more stable and heterogeneous microbiota during the storage phase and showed lower scores of Alternaria infectoria and A. alternata . In I-samples, volatilomics showed an increased relative concentration of volatile carboxylic acids. Therefore, without resorting to chemical preservatives, the addition of BCs and tIII-SD led to specific microbiological and metabolite improvements in both BP and FO products, whose shelf-life was extended by 10-days under MAP. Highlights: BCs and type-III sourdough can be useful to exert a bio-preservative effect in bakery products. BCs and type-III sourdough decrease the viability of spoilage microorganisms. BCs and type-III sourdough stabilize the microbiota and mycobiota profiles. BCs and type-III sourdough affect the volatile organic compound profiling of bakery products. BCs and type-III sourdough can allow for a 10-days shelf-life extension of bakery products.